Hypothalamic Amenorrhea and the Long-Term Health Consequences - Shufelt, Chrisandra L.; Torbati, Tina; Dutra, Erika (Seminars in Reproductive Medicine, 2017)
The menstrual cycle is a reproductive vital sign and provides insight into hormonal imbalance as well as pregnancy. The significance of estrogen, however, extends beyond fertility and plays a role on tissues and organs throughout the body. Functional hypothalamic amenorrhea is a common form of secondary amenorrhea resulting in estrogen deficiency in young premenopausal women. While reversible, the cause of this disorder is related to psychological stress, excessive exercise, disordered eating, or a combination of these factors resulting in suppression of the hypothalamic–pituitary–ovarian axis. The resulting loss of estrogen has profound effects on many systems throughout the body, including cardiac, skeletal, psychological, and reproductive. Often, these young women are “walking well,” as they do not have bothersome symptoms of low estrogen and are unaware of the consequences of estrogen deficiency. This review focuses on the health consequences of hypothalamic amenorrhea, current research, and available treatment options.
Keywords: amenorrhea; estrogen; cardiovascular; premenopause